The Expiration of IPO Share Lockups - Field, Laura Casares; Hanka, Gordon (Journal of Finance, 2001)
ABSTRACT We examine 1,948 share lockup agreements that prevent insiders from selling their shares in the period immediately after the IPO (typically 180 days). While lockups are in effect, there is little selling by insiders. When lockups expire, we find a permanent 40 percent increase in average trading volume, and a statistically prominent three‐day abnormal return of −1.5 percent. The abnormal return and volume are much larger when the firm is financed by venture capital, and we find that venture capitalists sell more aggressively than executives and other shareholders. We find limited support for several hypotheses that may explain the abnormal return, but no complete explanation.